Assessing the COVID-19 and Its Shocks on Macro-economic Variables in Nepal - Bista, Raghu Bir (Economic Journal of Development Issues, 2020)
This study assesses the COVID-19 and its shocks on macro-economic variables in Nepalese economy based on the secondary data sets of macroeconomics variable pre- and post-COVID-19 by applying descriptive statistical methods. The growth of COVID-19 is unpredictably spreading all over the world. Its hot spot has been in the South Asia, particularly in Delhi and Nepal. Its correlation between COVID 19 cases and per capita GDP is positive. In South Asia, its growth rate is higher than its recovery indicating inefficiency of health system. Similarly, its shocks are so strong to influence trend, pattern and structure of macro-economic variables. Economic growth declined at 0.1percent in 2020 with falling outputs of agriculture, industry and service sectors. Unemployment rate reaches at 27.8 percent from 11.4 percent. The poor population increased by 7.47 percent. Besides, residential income and household income has fallen along with sharp decline in labor and remittance income. Lastly, its negative implication is found in foreign exchange reserve and balance of payment, trade and revenue. Thus, the COVID-19 and its shocks are undesired fluctuations and impose implications in Nepalese economy. Therefore, Nepal should improve health care system and vaccine availability for reducing the effects of pandemic and the lockdown for stability and recovery of the economy and also for welfare of the poor.